Bis(methyl xanthato)-κS;κ2S:S′-(triphenylphosphane-κP)palladium(II) - Reyna Reyes-Martínez; Simón Hernández-Ortega; David Morales-Morales (Acta Crystallographica Section E, 2011)
The title compound, [Pd(C2H3OS2)2(C18H15P)], features a palladium complex with a triphenylphosphane ligand and two xanthate ligands, one of them coordinates in a bidentate and the other in a monodentate fashion, giving rise to a slightly distorted square-planar coordination of the PdII ion. As a result of this difference in the coordination modes, the C—S bond lengths are different, viz. 1.687 (2) and 1.692 (2) Å in the bidentate ligand and 1.723 (2) Å in the monodentate ligand, whereas the non-coordinating S atom has a C—S distance of 1.649 (2) Å. The crystal packing is stabilized by C—H...O interactions.